Implementasi E-Government Pada Pemilu 2024 - Yulianto (JCSE: Journal of Community Service and Empowerment, 2023)
Information and communication technology has grown rapidly and its use has become a necessity for business institutions and government institutions. This includes the use of information technology in the implementation of elections (e-democracy) both at the stage or pre-election period, election period and post-election period. The use of information and communication technology in elections is expected to increase the effectiveness, efficiency and transparency of election administration. Some of the challenges faced are related to the vast geography of the Indonesian state consisting of thousands of islands which has an effect on equitable distribution of information technology infrastructure, and limited human resource capabilities, especially at the polling station level. Socialization activities to the public about the use of information systems in organizing the 2024 elections are carried out to increase voter participation